Creative Design Training in the Gen Z Era: Teacher Training at Vocational Schools Using Canva for Innovative Learning Media: Pelatihan Desain Kreatif di Era Gen Z: Pelatihan Guru SMK Menggunakan Canva untuk Media Pembelajaran yang Inovatif - Sahputri, Desi Nori; Siswanto, Didik; Zamzami, Zamzami; Nijal, Lasri; Febriadi, Bayu; Agusviyanda, Agusviyanda (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
This study examines Canva training for teachers at SMK Muhammadiyah 2 Pekanbaru to enhance their skills in creating innovative and engaging learning media for Generation Z. This generation tends to prefer learning methods that are more visual and digital, making graphic design skills an important aspect to increase student engagement. The training was conducted using an interactive workshop approach, which included pre-and post-training surveys and direct classroom observation.The results show that this training successfully improved teachers’ skills in using Canva. Teachers were able to create learning media such as posters, presentations, and interactive quizzes tailored to modern students' learning styles. With more appealing media, student engagement in the learning process increased significantly, and the quality of learning improved.This study recommends integrating graphic design platforms like Canva into the educational curriculum to support a more creative and effective teaching-learning process. This integration is expected to drive educational innovation and provide students with a richer and more relevant learning experience in the digital era. Adopting this technology not only facilitates teaching but also motivates students to actively participate in learning activities, boosting their confidence and critical thinking skills suited to the demands of the modern era. Thus, Canva serves as a tool that supports sustainable education and adapts to the needs of today’s generation.